2015
DOI: 10.1007/s00592-015-0783-3
|View full text |Cite
|
Sign up to set email alerts
|

[I10W]tigerinin-1R enhances both insulin sensitivity and pancreatic beta cell function and decreases adiposity and plasma triglycerides in high-fat mice

Abstract: This study shows that [I10W]tigerinin-1R improves insulin sensitivity, islet function and glycaemic control in high-fat-fed mice and has potential as a template for development of novel anti-diabetic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This was associated with improved glucose tolerance following oral and intraperitoneal glucose administration accompanied by enhanced insulin secretion. These observations are broadly consistent with effects of tigerinin-1R [ 12 ], [I10W]-tigerinin-1R [ 30 ] and magainin-AM2 [ 13 ], suggesting a possible similar spectrum of actions in this animal model of obesity and diabetes. We have previously shown that the antidiabetic effects of magainin-AM2 [ 13 ] and [I10W]-tigerinin-1R [ 30 ] were accompanied by improvement in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was associated with improved glucose tolerance following oral and intraperitoneal glucose administration accompanied by enhanced insulin secretion. These observations are broadly consistent with effects of tigerinin-1R [ 12 ], [I10W]-tigerinin-1R [ 30 ] and magainin-AM2 [ 13 ], suggesting a possible similar spectrum of actions in this animal model of obesity and diabetes. We have previously shown that the antidiabetic effects of magainin-AM2 [ 13 ] and [I10W]-tigerinin-1R [ 30 ] were accompanied by improvement in insulin sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…These in vivo actions were greater with the [D28K] and [C31S] analogues while the in vitro insulinotropic actions of the other peptide analogues were not replicated in vivo . The in vivo effects of [L28K] and [C31K]esculentin-2CHa in these animals were more pronounced than those previously reported for other amphibian skin peptides [ 12 14 , 30 ]. Twice-daily administration of [L28K]esculentin-2CHa for 28 days did not affect body weight and food intake but reduced hyperglycaemia and elevated plasma insulin concentrations in the non-fasting state.…”
Section: Discussionmentioning
confidence: 49%
“…Consequently, the data provide further support for the contention that naturally occurring tigerinin peptides may serve as templates for the design of nontoxic and long-acting analogues for use in the treatment of patients with type 2 diabetes. 1,8,11 Cytokine Production. In the first series of experiments, all four tigerinins at a concentration of 20 μg/mL produced a significant (P < 0.05) decrease in the production and release of interferon-γ (IFN-γ) by peritoneal cells from C57BL/6 mice (Figure 6A).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Largely devoid of antimicrobial and cytotoxic properties, tigerinin-1R and its analogues , stimulate insulin release from BRIN-BD11 clonal β-cells and the release of glucagon-like peptide-1 (GLP-1) from the GLUTag cell line at concentrations that are not toxic to the cells. Studies in vivo have shown that tigerinin-1R and its analogues , enhance both insulin sensitivity and pancreatic β-cell function and decrease adiposity and plasma triglycerides when administered to mice given a high-fat diet to produce obesity and insulin resistance. In addition, tigerinin-1R increases production of the anti-inflammatory cytokine interleukin-10 (IL-10) in both spleen cells from C57BL/6 mice and human peripheral blood mononuclear cells without stimulating production of the pro-inflammatory cytokines interleukin-12 (IL-12) and interleukin-23 (IL-23), suggesting a possible role in the treatment of sepsis.…”
mentioning
confidence: 99%
“…In vitro studies have shown that it stimulates the release of insulin, even at concentrations as low as 0.1 nM, and exhibits no hemolytic activity against human erythrocytes at concentrations up to 500 nM [ 22 ]. In vivo studies have shown that administration of tigerinin-1R or some of its analogs to high-fat fed mice significantly enhanced insulin release and improved glucose tolerance [ 20 , 22 , 23 , 24 ]. Ojo et al suggests that a C-terminally amidated amino acid is necessary for the potency of the peptide.…”
Section: Introductionmentioning
confidence: 99%